PENGGUNAAN BOOTH STAND DAN MEMBANGUN EKONOMI DIGITAL BAGI PRODUK MEMBER UKM JASERCO DI KOTA SERANG - Hanafiah, Hafidz; Harsono, Pramudi; Chafid, Nurul; Susanto, Budi; Sofian, Ofan (Jurnal Abdimas Bina Bangsa, 2024)
This community service is carried out in order to advance SMEs from Jaserco members so that they are known and build networks at the Jaserco Gathering event carried out by the Jaserco Community, Jaserco Gathering 2023 Committee, representatives of lecturers from Bina Bangsa University and Satya Negara Indonesia University in the form of promoting SMEs and building digital economy in Serang City for Jaserco members who have businesses to be known by other community members. This activity was planned two months in advance with open booth promotions for both SMEs and sponsorships, then a simple booth was created that could be recognized and build a customer network through fellow members of Jaserco community in Serang City. The number of SME members of Jaserco is actually large, but approximately 10 SMEs participated with limited space and time. This activity aims to increase promotion of members who own UKM so that they are better known and build a digital UKM economy. This program will be planned regularly every year so that new SMEs emerge and motivate Jaserco members